Interference in vehicle-to-vehicle communication networks - analysis, modeling, simulation and assessment - Schmidt-Eisenlohr, Felix (KIT Scientific Publishing, 2010)
In wireless vehicular communication networks the periodic transmission of status updates by all vehicles represents a basic service primitive, in particular for safety related applications. Due to the limited communication resources the question raises how much data each node may provide such that the quality of service required by applications can still be guaranteed under realistic interference conditions. Local broadcasts capacity is introduced and analyzed to tackle this open question.